1966
DOI: 10.4141/cjps66-021
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON THE PERSISTENCE OF AVENA FATUA

Abstract: In an attempt-to.determiue the persi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
2
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 1 publication
1
24
2
1
Order By: Relevance
“…4. Comparison of the wild oat (A venafatua) putative aldose reductase amino acid sequence with that of bromegrass (Bromus inermis) [25] and barley (Hordeum vulgare) [3]. A dash ( -) indicates an amino acid match with the corresponding amino acid in wild oat aldose reductase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4. Comparison of the wild oat (A venafatua) putative aldose reductase amino acid sequence with that of bromegrass (Bromus inermis) [25] and barley (Hordeum vulgare) [3]. A dash ( -) indicates an amino acid match with the corresponding amino acid in wild oat aldose reductase.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, seed dormancy and longevity have been considered inseperable characteristics [2]. Embryo dormancy seems to be crucial for the long-term persistance of wild oat observed in some Canadian populations [3]. In contrast, wild oat lacking embryo dormancy have a relatively short persistence in the soil [41].…”
Section: Discussionmentioning
confidence: 99%
“…Late germinating families might tend to escape the selection sieve owing to the volatility of the herbicide, which ordinarily is applied to the soil in the autumn or in the early spring. Also, only a fraction of the population constituting the seed bank in the soil germinates in any given season, because some seeds are known to remain dormant but viable for as long as 7 years in soil (Banting 1966). In westem Canada, where summer fallowing is a common agronomic practice, selection favours genotypes which confer long-term seed dormancy.…”
Section: Discussionmentioning
confidence: 99%
“…Burying weed seeds with tillage operations increases the number of weed seeds in the soil seed bank and may cause these seeds to persist longer than seeds remained on the soil surface, potentially setting the stage for future weed problems. Banting (1966) found that wild oat seeds buried below a depth of 5 cm remained viable longer than seeds on the soil surface. More recently, Gulden et al (2003) found that canola seed lost during harvest could enter the state of secondary dormancy and persist for many years in the soil.…”
Section: Laboratory Experimentsmentioning
confidence: 99%